2017
DOI: 10.1097/wnr.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced cerebellar–cerebral functional connectivity alterations in nasopharyngeal carcinoma patients

Abstract: The current study aimed to investigate the altered cerebellar-cerebral functional connectivity (FC) induced by radiotherapy to nasopharyngeal carcinoma (NPC) patients. Twenty-four NPC patients without treatment, and 35 NPC patients receiving radiotherapy underwent functional MRI scanning. Montreal cognitive assessment (MoCA) was performed to evaluate the cognitive status of all participants. FC between 10 predefined cerebellar seeds, which were demonstrated to be involved in different brain functional networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…The method of PCA+SVM was quite helpful to improve the accuracy of the classification, and validly detected the abnormal brain regions, which widely contained the previous research achievement. As shown in Table 1, our results were consistent with previous studies, suggesting that the method was in favour of identifying the injury caused by RT [5][6][7]9]. The classification accuracy was 82.5 %, indicating that the method could well identify the abnormal changes induced by RT.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The method of PCA+SVM was quite helpful to improve the accuracy of the classification, and validly detected the abnormal brain regions, which widely contained the previous research achievement. As shown in Table 1, our results were consistent with previous studies, suggesting that the method was in favour of identifying the injury caused by RT [5][6][7]9]. The classification accuracy was 82.5 %, indicating that the method could well identify the abnormal changes induced by RT.…”
Section: Resultssupporting
confidence: 81%
“…The cerebellum was vital to the motor control, cognitive and affective regulation [7]. Shen et al [20] reported that the cerebral microbleeds (CMBs) observed in the cerebellum were related to cognitive dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion kurtosis imaging (DKI) can detect the early presence of relatively subtle radiation-induced changes before temporal lobe necrosis [25,26]. Altered brain functional connections were significantly correlated to the Montreal Cognitive Assessment scores in NPC patients, which may serve as a potential biomarker of the brain functional impairments [27,28]. Thus, structural and functional MRI were more sensitive than conventional MRI in determining radiation induced brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a research team has suggested that radiation can induce functional connectivity (FC) alterations using two independent samples (one group comprised untreated NPC patients and the other comprised NPC patients 6 months after receiving RT), but it is still difficult to directly and objectively demonstrate the functional changes because it is hard to avoid various confounders from two different samples in these studies. [14,15]…”
Section: Introductionmentioning
confidence: 99%